Peningkatan Kesadaran Lingkungan melalui Plang Edukasi Sampah di Pantai Wisata Kalomang, Kelurahan Watubangga - Hasmar, Wahyu Nuraini; Sudani, Ni Nyoman tri; Hasnal, Nopianti Sa'dan; Zizih, Andi Rezah Tenri; Ilmi, Annisa Nurul; Juanda, Juanda; Sabilla, Hijriya; Hasnal, M Raaf; Bela, Adel Salsa; Meilani, Meilani; Naniwijaya, Cahaya; intani, Reski amalia; Nurhalili, Nurhalili (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The problem of inorganic waste in tourist areas, such as Kalomang Beach, is pressing due to the low level of understanding among visitors and the local community regarding the impact and long decomposition time of waste. This lack of knowledge encourages littering behavior.This community service program aimed to enhance environmental awareness and change behavior through education. The methodology included observation, planning, and the installation of informative educational signboards. The main result was the development of an interactive educational signboard placed in strategic locations. These signs display real inorganic waste samples, such as plastic bottles (450 years) and plastic bags (20 years), along with their estimated decomposition times. The placement of the signs proved effective in attracting attention. Initial evaluations indicated an increase in awareness and several areas appearing cleaner. Although long-term evaluation is still required, the program successfully served as an important first step in triggering behavioral change. The implication is the effectiveness of education as a model for future sustainable environmental programs.